A Long‐Cycle‐Life Lithium–CO2 Battery with Carbon Neutrality. Issue 40 (22nd August 2019) - Ahmadiparidari, Alireza; Warburton, Robert E.; Majidi, Leily; Asadi, Mohammad; Chamaani, Amir; Jokisaari, Jacob R.; Rastegar, Sina; Hemmat, Zahra; Sayahpour, Baharak; Assary, Rajeev S.; Narayanan, Badri; Abbasi, Pedram; et al.
Abstract: Lithium–CO2 batteries are attractive energy‐storage systems for fulfilling the demand of future large‐scale applications such as electric vehicles due to their high specific energy density. However, a major challenge with Li–CO2 batteries is to attain reversible formation and decomposition of the Li2 CO3 and carbon discharge products. A fully reversible Li–CO2 battery is developed with overall carbon neutrality using MoS2 nanoflakes as a cathode catalyst combined with an ionic liquid/dimethyl sulfoxide electrolyte. This combination of materials produces a multicomponent composite (Li2 CO3 /C) product. The battery shows a superior long cycle life of 500 for a fixed 500 mAh g −1 capacity per cycle, far exceeding the best cycling stability reported in Li–CO2 batteries. The long cycle life demonstrates that chemical transformations, making and breaking covalent CO bonds can be used in energy‐storage systems. Theoretical calculations are used to deduce a mechanism for the reversible discharge/charge processes and explain how the carbon interface with Li2 CO3 provides the electronic conduction needed for the oxidation of Li2 CO3 and carbon to generate the CO2 on charge. This achievement paves the way for the use of CO2 in advanced energy‐storage systems. Abstract : A fully rechargeable long‐cycle‐life Li–CO2 battery is presented, and its carbon‐neutral reversibility is shown using various in situ and ex situ techniques. The long cycle life of this battery demonstrates that complex chemical transformations, making and breaking CO bonds, can be used in energy‐storage systems.